Strangeness production in fixed-target collisions at LHCb - Lucarelli Chiara (EPJ Web of Conferences)
Studies of strangeness production in high-energy fixed-target collisions provide information on hadronization and serve as important inputs to models of particle production in cosmic rays. Thanks to its forward geometry and the possibility to inject gas into the beam pipe, the LHCb detector with the SMOG system is ideally suited to study strangeness production in fixed-target collisions at the LHC. We present recent LHCb results on strangeness production in fixed-target proton-nucleus collisions, including studies of hyperon production and polarization.